Transit From Autotrophism to Heterotrophism: Sequence Variation and Evolution of Chloroplast Genomes in Orobanchaceae Species - Zhang, Ruiting; Xu, Bei; Li, Jianfang; Zhao, Zhe; Han, Jie; Lei, Yunjing; Yang, Qian; Peng, Fangfang; Liu, Zhan-Lin (Frontiers in Genetics, 2020)
The family Orobanchaceae including autotrophic, hemiparasitic, and holoparasitic species, is becoming a key taxa to study the evolution of chloroplast genomes in different lifestyles. But the early evolutionary trajectory in the transit from autotrophism to hemiparasitism still maintains unclear for the inadequate sampling. In this study, we compared 50 complete chloroplast genomes in Orobanchaceae, containing four newly sequenced plastomes from hemiparasitic Pedicularis, to elucidate the sequence variation patterns in the evolution of plastomes. Contrasted to the sequence and structural hypervariabilities in holoparasites, hemiparasitic plastomes exhibited high similarity to those of autotrophs in gene and GC contents. They are generally characterized with functional or physical loss of ndh/tRNA genes and the inverted small-single-copy region. Gene losses in Orobanchaceae were lineage-specific and convergent, possibly related to structural reconfiguration and expansion/contraction of the inverted region. Pseudogenization of ndh genes was unique in hemiparasites. At least in Pedicularis, the ndhF gene might be most sensitive to the environmental factors and easily pseudogenized when autotrophs transit to hemiparasites. And the changes in gene contents and structural variation potentially deeply rely on the feeding type. Selective pressure, together with mutational bias, was the dominant factor of shaping the codon usage patterns. The relaxed selective constraint, potentially with genome-based GC conversion (gBGC) and preferential codon usage, drive the fluctuation of GC contents among taxa with different lifestyles. Phylogenetic analysis in Orobanchaceae supported that parasitic species were single-originated while holoparasites was multiple-originated. Overall, the comparison of plastomes provided a good opportunity to understand the evolution process in Orobanchaceae with different lifestyles.